Implementation of The Family Hope Program in Poverty Reduction in Cilimus Village Teluk Pandan District Pesawaran Regency - Lies Kumara Dewi; Eka Ubaya Taruna Rauf; Husna Purnama; Adi Pramana (Pusat Riset Manajemen dan Publikasi Ilmiah Serta Pengembangan Sumber Daya Manusia Sinergi Cendikia, 2022)
The issue of poverty in Indonesia is a social problem that is consistently applicable to be concentrated without stopping and demands the interests of all parties jointly and facilitated. The Family Hope Program or Program Keluarga Harapan (PKH) provides non-cash assistance to The Very Poor Family or Rumah Tangga Sangat Miskin to meet mandatory needs. However, the implementation of PKH still has many shortcomings. This study aims to find and analyze the reality of the extent of the Implementation of the Family Hope Program in Poverty Reduction in Teluk Pandan, Pesawaran Regency. The strategy used is an expressive technique with a subjective methodology, with strategies for gathering information on perceptions, meetings and documentation. The results show that the implementation of PKH has not been effective, there are still many poor people who have not received PKH benefits, and PKH recipients do not have the awareness not to accept PKH for people who are already prosperous. Thus, the implementation of the Peraturan Menteri Sosial Republik Indonesia Nomor 1 Tahun 2018 tentang Program Keluarga Harapan is considered not yet ideal in assisting the government for all residents in Cilimus Village.